PLC-HMI BASED SIMULATION of PV CELL and ARRAY BEHAVIOR - Fadhil, Maytham Ali; Mahmood, Jawad Radhi (Iraqi Journal for Electrical and Electronic Engineering, 2019)
This paper presents the PLC-HMI based simulation of electrical-based PV cell/array model in laboratory platform to give the opportunity to students and users who haven’t clear knowledge to study PV cell and array behavior with respect to change of environment conditions and electrical parameters. This simulation process covers the cell models under ideal and non-ideal ones. In non-ideal one, the series resistance and the shunt resistance are covered.